Prevention of work related skin problems: an intervention study in wet work employees. Issue 8 (1st August 2002) - Held, E; Mygind, K; Wolff, C; Gyntelberg, F; Agner, T
Abstract : Aims: To evaluate the effect of implementation of an evidence based skin care programme for wet work employees as part of an occupational health and safety management system. Methods: 375 wet work employees were included in a prospective randomised controlled trial, allocated to either intervention (n = 207) or control (n = 168). The intervention group was exposed to a skin care programme during the five month study period. The intervention included an educational programme for a group of frontline employees, who underwent formalised training, and subsequently introduced the information to their colleagues. As part of the intervention a skin care policy including written instructions was established at each workplace. Both groups answered a test quiz, completed questionnaires on behaviour and symptoms, and underwent clinical examination of their hands before and after the five month period. Results: No difference between the intervention and the control group was found at baseline with respect to clinical symptoms or behaviour. Evaluation after the five months of intervention revealed a significantly higher information level on skin care in the intervention group compared to the control group, a significant change in behaviour in the intervention group but not in the control group, and significantly less skin symptoms as evaluated clinically in the intervention group but not in the control group. No significant difference was found for self reported skin problems. Conclusions: The intervention was successful with respect to information level (knowledge), behaviour, and clinical symptoms. Implementation of a skin care programme as part of an occupational health and safety management system is recommended as a prophylactic measure for employees in wet occupations.